The Effect of Education Policy on Crime: An Intergenerational Perspective - Meghir, Costas
The Swedish comprehensive school reform implied an extension of the number of years of compulsory school from 7 or 8 to 9 for the entire nation and was implemented as a social experiment by municipality between 1949 and 1962. A previous study (Meghir and Palme, 2005) has shown that this reform significantly increased the number of years of schooling as well as labor earnings of the children who went through the post reform school system, in particular for individuals originating from homes with low educated fathers. This study estimates the impact of the reform on criminal behavior: both within the generation directly affected by the reform as well as their children. We use census data on all born in Sweden between 1945 and 1955 and all their children merged with individual register data on all convictions between 1981 and 2008. We find that the educational reform decreased crime substantially for men who were directly affected by it. We also find that the crime rate declined for the sons of those fathers directly affected by the new educational system; we interpret this results as implying that improved education increased resource and parenting quality, leading to improved child outcomes.Comprehensive school; economics of crime; returns to education; returns to human capital